PENERAPAN METODE PEMBIMBINGAN KLASIKAL UNTUK MENINGKATKAN KEMAMPUAN MENYUSUN KARYA TULIS ILMIAH GURU DI SD 2 SUMBERAGUNG - Rahayu, Rustini (universitas Ahmad Dahlan, 2020)
The purposes of this research are (1) to improve the teachers’ scientific writing ability based on classical guidance method in 2 Sumberagung Primary School. (2) The implementation of classical guidance method to teachers in compile the scientific papers in 2 Sumberagung Primary School. This research was a school action research. The research method went through two cycles. Research data obtained by observation sheets. The result of each cycle were analyzed and then used as reference material for the next action. Technical analysis used descriptive analysis. The success rate of teacher competency was in able category reached 75%. The implementation of classical guidance method in 2 Sumberagung Bantul Primary School carried out through three stages, those were preparation, the implementation and the evaluation phase. The ability of the mentor in conducting classical mentoring in the first cycle was in the quite good category with a score as much 50% and the score it increased to 100% with a very good category in the second cycle. The classical guidance method was able to improve the teacher's professional competence in compile their scientific papers at 2 Sumberagung Primary School. This was evidenced by the increased of the teachers’ ability in compile their scientific papers at this time as much 78.5%.